Pengaruh Metode Tutor Sebaya Terhadap Hasil Belajar Siswa Pada Materi Pembagian Dengan Bilangan Dua Angka Di Kelas IV SD Negeri 2 Rantau Selamat Aceh Timur - Mahfudz, Idsan Lauhil; Fauzi, Fauzi; Yamin, M. (Universitas Syiah Kuala, 2023)
The problem here is that the teacher only applies the lecture method and practice questions so that it affects student learning outcomes that do not meet the Minimum Learning Criteria (KBM). The purpose of this study was to investigate the effect of the significance of the peer tutoring method on student learning outcomes in the matter of dividing by two-digit numbers in class IV SD Negeri 2 Rantau Selamat. The method taken is quantitative and uses the type of Pre-Experimental Design. The data collection technique used in this study was a test in the form of pretest and posttest. The data analysis technique taken is the SPSS Statistics 24 application. The decision making category is H0 rejected and H1 accepted. So it can be concluded that there is a significant effect of the use of the peer tutoring method on student learning outcomes in the division material with two-digit numbers in class IV SD Negeri 2 Rantau Selamat Aceh Timur.